1909
DOI: 10.5962/bhl.title.5397
|View full text |Cite
|
Sign up to set email alerts
|

Researches on fungi

Abstract: 1 6 RESEARCHES OX FrXGT essential function of producing spores. Instances of sterility ot this kind have been noticed in two different species. A board was found in a cellar infected with Coprinus fimetarius, var. cinereus, and a small piece of it, bearing a young fruit-body, was sawn off, brought to the laboratory, and placed in a danip-chainber. After further development the fruit-body attained average size and form, but exhibited the peculiarity of being yellowish-white in colour instead of ashy grey. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
148
0
2

Year Published

1914
1914
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 0 publications
4
148
0
2
Order By: Relevance
“…Whether this clamped mycelium is formed from two compatible homokaryons, or from a homokaryon and a heterokaryon is not important, for it has been shown that the dikaryotization of a homokaryon by a heterokaryon-the Buller Phenomenon (Buller 1931)-is as good evidence of conspecificity as the formation of a heterokaryon from two homokaryons (Terra 1959;Boidin and des Pomeys 1961;Nobles and Frew 1962;Raper 1966). The essential feature of either process is that two compatible nuclei, capable of conjugate division, are brought together in one cell, and manifest their presence by producing hyphae bearing clamped septa.…”
Section: Dikaryotizationmentioning
confidence: 99%
“…Whether this clamped mycelium is formed from two compatible homokaryons, or from a homokaryon and a heterokaryon is not important, for it has been shown that the dikaryotization of a homokaryon by a heterokaryon-the Buller Phenomenon (Buller 1931)-is as good evidence of conspecificity as the formation of a heterokaryon from two homokaryons (Terra 1959;Boidin and des Pomeys 1961;Nobles and Frew 1962;Raper 1966). The essential feature of either process is that two compatible nuclei, capable of conjugate division, are brought together in one cell, and manifest their presence by producing hyphae bearing clamped septa.…”
Section: Dikaryotizationmentioning
confidence: 99%
“…The pycnia maybe functionally suppressed gradually during evolution from heterothallism to homothallism (Buller 1950). This was shown in Puccinia coronata Cda., a remarkable species which has 4 varieties, P. coronata avenae F. and L., P. coronata calamagrostidis F. and L., P. coronata bromi F. and L. and P. coronata elaegni F. and L., in which the first 2 varieties are heterothallic with well-developed pycnia (Allen 1932, Buller 1950. P. coronata elaegni is homo thallic with vestigial pycnia (Brown and Craigie 1938).…”
Section: Discussionmentioning
confidence: 86%
“…Both R. breyniae and R. sessilis produce respectively modera tely and well-developed pycnia, but both lack nectar ooze. Buller (1950) stated that presence of a pycnium cannot be a criterion to conclude that the species is homothal lic. On the contrary, Jackson (1935) opinioned that the presence of spermogonia and spermatia should not be considered indisputable evidence that the species is homothallic.…”
Section: Discussionmentioning
confidence: 99%
“…The unsatisfactory nature of disease-forecasting systems based on the determination of period of conidial liberation in the field (paddick, personal communication) may well be explained by the operation of such a mechanism. Sussman and Halvorson (1966) provide data showing a direct relationship between longevity and water content of fungal spores, but instances are known where dehydration rapidly leads to death (Buller 1933;Glaz 1955). In the present study, the results shown in Table 2 indicate a strong interaction between the effects of storage humidity and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…INTRODUCTION Gregory (1961) has noted that, in air, spores gain orlose water rapidly. A number of studies (Buller 1909(Buller , 1922Falck 1927;Weinhold 1955) have been made on the sedimentation of spores in still air and the effects of desiccation on their rates of fall, but fewer authors have investigated the effects of desiccation on other properties of spores. Grindle and Good (1961) and Good and Zathurecsky (1967) have studied the effects of drying on the viability of germinating and germinated conidia of several fungi.…”
mentioning
confidence: 99%